2002
DOI: 10.1089/08892220260190317
|View full text |Cite
|
Sign up to set email alerts
|

Role of Placental Cytokines in Transcriptional Modulation of HIV Type 1 in the Isolated Villous Trophoblast

Abstract: During pregnancy, a complex cytokine network is present at the maternal-fetal interface in order to support normal growth and development of the placenta and fetus. HIV can frequently infect placental trophoblast but the impact of cytokines produced locally by the placenta and decidua on virus expression and replication is unknown. We comprehensively assayed the cytokines typically present in the placental microenvironment for their potential to modulate HIV transcriptional activation in the isolated trophobla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 57 publications
(45 reference statements)
4
25
0
Order By: Relevance
“…Interestingly, the same cytokines also induced viral transcription in trophoblastic cells exposed to replication-defective reporter viruses bearing HIV-1 Ada-M or HXB2 envelope glycoproteins. These findings are supported by a recent study (44) showing that HIV-1 LTR activity is increased by TNF-␣ and IL-1␤ in primary isolated human trophoblast cells that were transiently transfected with an HIV-1-based reporter vector. Data from this study were entirely based on transient transfection of HIV-1 LTR-based reporter constructs in trophoblast cells.…”
Section: Discussionsupporting
confidence: 83%
“…Interestingly, the same cytokines also induced viral transcription in trophoblastic cells exposed to replication-defective reporter viruses bearing HIV-1 Ada-M or HXB2 envelope glycoproteins. These findings are supported by a recent study (44) showing that HIV-1 LTR activity is increased by TNF-␣ and IL-1␤ in primary isolated human trophoblast cells that were transiently transfected with an HIV-1-based reporter vector. Data from this study were entirely based on transient transfection of HIV-1 LTR-based reporter constructs in trophoblast cells.…”
Section: Discussionsupporting
confidence: 83%
“…Furthermore, the present data showing that PBMCs incubated overnight with PSF and then inoculated with HIV-1 produced 100 to 1,000 times less virus than untreated PBMCs further support a role of PSF in con- trolling spreading of HIV-1 through the placenta, after passage across the trophoblastic barrier. We addressed the question of whether this anti-HIV-1 activity was related to IFN-like activity in PSF since previous studies demonstrated that placental cells secreted this antiviral cytokine (19,33). Thus, the level of secretion and the mRNA content of several forms of IFN in both placental tissue and PSF were evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, expression of inflammatory cytokines is elevated in trophoblasts with a high level of HIV transcripts (18). Along with these findings, interleukin-1␤ (IL-1␤) and tumor necrosis factor alpha (TNF-␣) were found to stimulate the transcriptional activity of HIV long terminal repeats expressed transiently in isolated trophoblast cells (33) or in trophoblastic cell lines infected with HIV-1 particles pseudotyped with HIV-1 envelope glycoproteins (32), whereas alpha interferon (IFN-␣) and IFN-␤ suppress the transcription driven from the viral promoter (33). Moreover, a correlation between in utero transmission of HIV-1 and expression of Th2 cytokines (IL-4 and IL-10) and leukemia inhibitory factor (LIF) has been reported (3,26).…”
mentioning
confidence: 81%
“…55 Interferon-a (IFN-a) and IFN-b inhibit the HIV transcription. 56 A connection between in utero vertical transmission of HIV-1 and expression of Th2 cytokines (IL-4 and IL-10) and LIF has been described. 25,52 Whether these factors may possibly limit HIV-1 infection of the trophoblasts remains to be clarified.…”
Section: Chemokinesmentioning
confidence: 99%